1998
DOI: 10.1038/sj.bmt.1701494
|View full text |Cite
|
Sign up to set email alerts
|

Successful cryopreservation of purified autologous CD34+ cells: influence of freezing parameters on cell recovery and engraftment

Abstract: Summary:Conventional hematopoietic stem cell cryopreservation methods use a DMSO concentration of 10%. However, cells manipulated ex vivo may require more refined freezing protocols adapted to the specific cell suspension. In this retrospective study, we evaluated the results obtained with CD34 ؉ cells purified from peripheral blood of 39 patients on the CEPRATE SC System and frozen in 7.5% DMSO with a view to transplantation. ؉ cells and CFU-GM were significantly related to hematological recovery. Our data su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 23 publications
5
31
1
Order By: Relevance
“…Recently, there have been several reports suggesting that cells can be successfully cryopreserved with minimal concentrations of DMSO [39][40][41][42][43][44][45][46][47][48][49][50][51]. For example, Zhao et al [46] showed that the use of 5% or 10% DMSO in combination with either 20% or 70% serum produced similar results during cryopreservation of fetal human liver CD34 + cells.…”
Section: Discussionmentioning
confidence: 74%
“…Recently, there have been several reports suggesting that cells can be successfully cryopreserved with minimal concentrations of DMSO [39][40][41][42][43][44][45][46][47][48][49][50][51]. For example, Zhao et al [46] showed that the use of 5% or 10% DMSO in combination with either 20% or 70% serum produced similar results during cryopreservation of fetal human liver CD34 + cells.…”
Section: Discussionmentioning
confidence: 74%
“…These results are comparable with recovery data reported after cryopreservation of PBSC (70-90% for nucleated cells, 33-80% for committed progenitors. 12,[30][31][32][33][34][35] In the experiments described in Table 4, three washes were performed before the addition of medium. As a consequence, recovery data were variable.…”
Section: Discussionmentioning
confidence: 99%
“…However, the inevitable loss of CD34 þ cells between collection and transplant, especially during cryopreservation, is difficult to predict without assessment of the sample after cryopreservation. 4,5,7,8,18 This leads to the current debate as to whether the quantification of HPC should be performed before or after cryopreservation.…”
Section: Cd34mentioning
confidence: 99%
“…5 In addition, the reported viability of CD34 þ cells varied from 0 to 304%. 4,8 This wide variation of the post-cryopreservation viability resulted from the post-thaw assessment assays being based on the number of nucleated cells remaining after cryopreservation. 9,10 However, the number of nucleated cells, particularly neutrophils, is decreased during cryopreservation and during post-thaw incubation due to cell loss and clumping of the damaged cells.…”
Section: Cd34mentioning
confidence: 99%